2003
DOI: 10.1603/0022-0493-96.6.1935
|View full text |Cite
|
Sign up to set email alerts
|

Do Rice Hybrids Have Heterosis for Insect Resistance? A Study with <I>Nilaparvata lugens</I> (Hemiptera: Delphacidae) and <I>Marasmia patnalis</I> (Lepidoptera: Pyralidae)

Abstract: Antibiosis-based resistance to two insect pests of rice, Nilaparvata lugens (Stål) (Hemiptera: Delphacidae) and Marasmia patnalis Bradley (Lepidoptera: Pyralidae), was compared in 11 F1 hybrids and their parental lines. Our objective was to determine whether hybrids show heterosis (hybrid vigor) for insect resistance or susceptibility. Heterosis is defined as the amount by which a hybrid exceeds its midparent value or its better parent. Overall, we did not find evidence of heterosis or heterobeltiosis (a type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…In our greenhouse experiment with 15 hybrid varieties and their parental lines, we noted that only one A line (IR70369A) was associated with susceptibility to BPH and WBPH in some resulting hybrids. Cohen et al (2003) [ 37 ] found similarly low variability across BPH responses to hybrids and their parental lines using a different range of hybrids from the same breeding program. Susceptibility related to IR70369A was more consistent in our experiments with BPH than WBPH (i.e., other lines derived from IR70369A tended to also have high numbers or a high biomass of BPH, but not of WBPH: Tables S2 and S5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our greenhouse experiment with 15 hybrid varieties and their parental lines, we noted that only one A line (IR70369A) was associated with susceptibility to BPH and WBPH in some resulting hybrids. Cohen et al (2003) [ 37 ] found similarly low variability across BPH responses to hybrids and their parental lines using a different range of hybrids from the same breeding program. Susceptibility related to IR70369A was more consistent in our experiments with BPH than WBPH (i.e., other lines derived from IR70369A tended to also have high numbers or a high biomass of BPH, but not of WBPH: Tables S2 and S5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The B line is required to maintain A line seed. The B line has the same nuclear genome as the A line, but has a distinct cytoplasmic genome that permits the production of viable pollen [5,37]. The restorer lines are more genetically diverse than the A and B lines and are selected based on their ability to combine with the A line to restore fertility [5,16].…”
Section: Plant Materialsmentioning
confidence: 99%
“…The B line is required to maintain A line seed. The A and B lines share the same nuclear genome but have distinct cytoplasmic genomes that bestow sterility to the A line [ 5 , 25 ]. We arbitrarily selected the eight hybrids ( Table S1 ) and their associated parental lines from the IRRI breeding program, with no a priori considerations except that a sufficient number of seeds should be available for the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Heterosis can be enhanced by increasing the genetic distance between parental lines [ 22 , 23 ]; this will also limit the movement of certain pests, such as planthoppers, between fields with different hybrid rice varieties [ 1 , 24 ]. Breeders can further avoid herbivore-susceptible parental lines and promote specific combinations of parental lines that achieve heterobeltiosis for herbivore resistance [ 11 , 25 , 26 ]. However, there are limitations on the choice of parents for hybrid breeding programs, as not all lines can restore fertility [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation